Nutritional Habits and Weight Status among Jazan University Students: Eating Patterns and Healthy lifestyle Assessment - Mohamed S Mahfouz; Anwar M Makeen; Ameera Y Akour; Tasneem M Madkhly; Hanouf M Hakami; Wejdan M Shaabi; Asrar F Ageeli; Fatmah A Khawaji; Kadejah A Najmi; Sarah Y Hakami; Mozynah A Al-Ali (Epidemiology, Biostatistics and Public Health)
Objectives